Public opinion towards healthcare in the context of economic crisis: evidence from Portugal - Popic, T.; Schneider, S.; Asensio, M. (Journal of Social Policy, 2019)
This article investigates to what extent austerity-oriented measures introduced in the Portuguese health sector during the recent economic crisis were associated with changes in the public opinion on healthcare. We conducted multivariate regression analyses of cross-sectional, biannual data from the European Social Survey (2002–2015) for 13,271 individuals living in private households in Portugal. In line with our expectations, healthcare evaluations of the general population improved until 2010 but declined with the implementation of comprehensive austerity measures introduced under the Memorandum of Understanding after 2011. Healthcare evaluations of vulnerable social groups – older and retired individuals, individuals with poor health, low income and education – declined particularly strongly. In addition, differences in healthcare evaluations between more and less vulnerable social groups were more pronounced after 2011. Interestingly, healthcare evaluations of the general population and of some of the most vulnerable groups ‘recovered’ in 2015, when most of the Memorandum measures were implemented. Our findings contribute to the literature on the effects of austerity measures on welfare attitudes and stress the need to analyse the differential impact of crisis-induced welfare state reforms across social groups.